Identification of Secondary Metabolites from Origanum majorana L. (Lamiaceae) Essential Oil Cultivated in Island of Djerba; Antibiofilm, Anticoagulant and Phytotoxic Properties - Bouomrine, Sonia; Melliti, Marwa; Harzallah-Skhiri, Fethia; Jannet, Hichem Ben; Faisal, Mohammad; Alatar, Abdulrahman A.; Flamini, Guido; Edziri, Hayet (Chemistry Africa, 2025)
Origanum majorana L. is an aromatic plant from the Lamiaceae family, considered as one of the popular plants in Tunisia since it was known to have many biological potentials and frequently grown in gardens as a condiment plant. The aim of this work is to explore the chemical composition, the antimicrobial, antibiofilm, anticoagulant and insecticidal activities of the flowering aerial parts extracts and the essential oil (EO) of this plant. The essential oil was extracted by hydrodistillation and analyzed using GC/MS. Polyphenols, flavonoids and tannins were quantified from three organic extracts. The antimicrobial activities were assessed against 8 bacteria; 4 Gram negative and 4 Gram positive ones; and 4 fungal strains. The biofilm inhibition was determined in vitro by the micro dilution method against 3 bacteria. Prothrombin time (PT) and kaolin clotting time (KCT) tests were employed to investigate the anticoagulation potential for the first time. The repellent activities of the organic extracts and the fumigant activity of the EO were studied. The flowering aerial parts EO is rich in oxygenated monoterpenes (54.38%) especially in terpinen-4-ol. For the antimicrobial activities, the tested oil displayed moderate antibacterial and antifungal activity (MIC = 1.5 mg/mL), and showed a good antibiofilm activity against the tested bacteria with inhibition values greater than 51 ± 1.04% at MIC dose. Furthermore, it has anticoagulant activities with a prothrombin time of 37.3 ± 0.36 s and KCT of 48.1 ± 0.26 s at a concentration of 15 mg/mL, as well as fumigants activities against Tribolium castaneum. Polyphenols and tannins contents were found to be the highest in ethyl acetate and ethanolic extracts. The two extracts showed interesting antibacterial and antifungal activity with values of MIC ranging from 1.25 to 10 mg/mL, and from 2.5 to 20 mg/mL, respectively. Also, they present a strong antibiofilm activity at different MICs. Ethyl acetate extract has an interesting anticoagulant activity at a concentration of 0.5 mg/mL with 52.18 ± 0.49 s for KCT. Ethanolic extract is a promising anticoagulant agent (16.9 ± 0.02 s for PT and 45.72 ± 0.24 s for KCT at a concentration of 0.5 mg/mL). Only Petroleum ether extract has repellent activities (62.5 ± 8.5%) against an insect pest tested. The aerial parts of Origanum majorana could be considered as new source of anticoagulant, antibiofilm, antibacterial, antifungal and insecticide molecules for pharmaceuticals and pest purposes. However, further research must be undertaken to identify the active molecules responsible for these biological activities.
Keywords: Botanique – Djerba

النخلة بين الخصوصية الجزيرية والمشترك القاري - الجزيراوي, محمد; السلاوتي, نجيب (2025)
"تعدّ النّخلة في جزيرة جربة ملكة الشجر إذ أنّها تغطي الجزء الأكبر من فضاء الجزيرة وتهيمن على مشهدها الطبيعي بشكل لا يمكن معه أن نتخيل منظرا جريبًا دون ""عش نخيل"" ذي ارتفاع يتراوح بين العشرة أو العشرين مترا. يتوزّع النخيل بشكل غير منتظم نسببًا: فنجده بمركز الجزيرة مصحوبا بأشجار أخرى، بينما يغطي المتاحل شريط متفاوت الأساع. لا يوجد الجزيرة تجمعا كثيفا للنخيل مثلما هو الشأن في لواحات القارية وذلك لضعف تربتها ولانعدام الينابيع والأنهار ورغم ذلك فالنخلة إستعمالات ديدة تتجاوز الحاجيات المادية المباشرة المرتبطة ضمان العيش وتحقيق البقاء بفعل حضور لمواد المستخرجة منها فى صنائع عدّة ناميك عن الأبعاد الرمزية الأسطورية التى ساقلها الجماعات جيلا بعد جيل وتتجلى فى بعض ممارس انهم العقائدية التى نميط اللثام عن شبكة العلاقات الإجتماعية. ستحاول هذه المداخلة من خلال تعتب المعارف والمهارات والممارمات المرتبطة بالنخلة في مختلف ناصر التراث الثقافي المادي وغير المادي، أولا : إثارة سؤال حول الخصوصيات الجزيرية، ثانيا: دراسة مقارنة مع مجال غير جزيري يعرف نفس العنصر ألا وهو منطقة نفزاوةٌ من الجنوب الغربي التونسي."
Keywords: Botanique – Djerba

An anthropogenic site for Riella Mont. (Riellaceae, Sphaerocarpales) in Djerba (Tunisia) - Ben Osman, Imen; Hugonnot, Vincent; Daoud-Bouattour, Amina; Muller, Serge D. (Journal of Bryology, 2024)
Four species of Riella were discovered in a small anthropogenic temporary pond on Djerba island (southern Tunisia). Riella bialata Trab. is not only a very rare species worldwide, but also a new record for Tunisia, and R. cossoniana Trab., R. macrocarpa (P.Allorge) Puche, Segarra-Moragues, Sabovlj., M.Infante & Heras, and R. notarisii (Mont.) are confirmed from Tunisia. Observations from fieldwork were combined with the results of spore culture to understand the presence of the species in this habitat. Significant differences in development, life strategy and ecology were hypothesised to promote the existence of the four Riella species in a small pond. Conservation issues were raised due to the anthropic origin of the habitat, emphasising the site’s ecological significance and vulnerability.
Keywords: Botanique – Djerba

Le « Gazoul », l'or vert des Djerbiens en Tunisie - Pouvoir antioxidant et antimicrobien de l'Allium roseum var. odoratissimum - Touihri, Barakati imen (Edition universitaire européenne, 2022)
Keywords: Botanique – Djerba

Micropropagation of apple (Malus domestica L. cultivar Douce de Djerba) through in vitro culture of axillary buds - Boudabous, Manel; Mars, Mongia; Marzougui, Nidhal; Ferchichi, Ali (Acta Botanica Gallica, 2010)
A high frequency of sprouting (85.0%) and shoot differentiation is observed in the primary cultures of nodal explants of Malus domestica L. cultivar Douce de Djerba on MS medium supplemented with BAP (1.0 mg.L−1) plus IBA (0.1 mg.L−1). In vitro proliferated shoots are multiplied rapidly by culture of shoot tips on MS medium with BAP (1.0 and 2.0 mg.L−1) which produce the greatest multiple shoot formation. The BAP has a positive effect on the multiplication and growth, but a concentration that exceeds 4.0 mg.L−1 decreases the growth. A high frequency of rooting (66.7%) with development of healthy roots is observed from shoots cultured on half strength MS medium enriched with IBA (3.0 mg.L−1) and 2.0 g.L−1 of activated charcoal. Plants with well developed roots were transferred to soil with a survival frequency of 60%.
Keywords: Botanique – Djerba

Distribution and Habitat Requirements of Zostera Noltei Along the Northern Coast of Jerba Island (southern Tunisia, Mediterranean Sea) - Shili, Abdessalem; Ben Hmida, A.; Ben Maiz, Naceur; Boudouresque, C.F. (Actes du 5ème symposium méditerranéen sur la végétation marine. Portorož, Slovenie, 27-28 octobre 2014, 2014)
Keywords: Botanique – Djerba

Epidemiological investigation of keratinophilic fungi from soils of Djerba (Tunisia) - Anane, S. (Journal de Mycologie Médicale, 2012)
Keywords: Botanique – Djerba

Olive groves: "The life and identity of the Mediterranean'' - Loumou, Angeliki; Giourga, Christina (Agriculture and Human Values, 2003)
Olive tree cultivation in theMediterranean goes back to ancient times. Evensince the Roman Age, olive cultivation spreadto the entire Mediterranean basin. Thislongevous tree integrates and identifieseconomically, socially, and culturally theinhabitants of this basin and determines itsrural landscape. For the residents of theMediterranean, olive oil constituted the mainsource of nutritional fats, their most valuableexport product, and was identified with theirculture. Even now, olive cultivation has amultiple importance for the Mediterranean. Theolive groves, which grow mostly on inclined,shallow, and low fertility soils, and onhand-made stone terraces, have limited wateringrequirements and sustain the fragile naturalresources of the Mediterranean. Today,olive cultivation in the Mediterranean is anadditional income source and supports thepopulation in rural areas during the winterperiod, which profit from summer and seatourism activity. Although anagro-ecosystem, the olive grove resembles thenatural Mediterranean ecosystem and abandonmenttransforms them into natural Mediterranean typeforests. Their change of use from olivecultivation to pasture degrades the ecosystemand decreases the natural resources, because ofover-grazing. At this time, two major factorsthreaten the traditional olive cultivation (i)the competition of the intensive olive grovesin plain and irrigated areas and (ii) thecheaper seed-oils, which intensify theabandonment of traditional olive groves andchange them into pasture, resulting in thedeterioration of the ecosystem. Olivecultivation has left its mark on life in theMediterranean and has contributed to thesustainability of natural resources.Nevertheless, it succumbs under the pressure ofcurrent socioeconomic situations. Today, theconservation of olives in productionconstitutes a necessity for the fragileMediterranean ecosystems and a challenge foreverybody involved.
Keywords: Botanique – Djerba

Que mangeaient les lotophages ? Contribution de l’ethnobotanique maghrébine à l’interprétation d’un passage de l’Odyssée - Bellakhdar, Jamal (Revue des Etudes Anciennes, 2016)
Keywords: Botanique – Djerba

Ethnobotanical study of medicinal plant in Djerba island, Tunisia - Ben Salah, Myriam; Barhoumi, Tarek; Abderraba, Manef (Arabian Journal of Medicinal and Aromatic Plants, 2019)
Objective :The aim of this study was to document the diversity and use of natural plants in the island of Djerba (Tunisia) in traditional pharmacopoeia and other uses in order to develop an ethnobotanical catalogue that could subsequently be the subject of scientific research.Materials and Methods: The technique of semi-structured interviews was used with people originating and residing or not in Djerba. Occasional conversations and direct observations were exploited for one year.Results: We have identified 86 plants out of 122 mentioned belonging to 80 genera and 43 families. Asteraceae were the most important family represented by 13 species followed by Lamiaceae and Poaceae (7 species each). The results showed that 45 species have medicinal uses (52.32%). Leaves were the most used parts (59% of species for medicinal use). Decoction was the most common method for preparing remedies.Conclusion: This study provides an important source of information for flora valorization in the studied region. The results could form a database for the search of new natural substances with added value.
Keywords: Botanique – Djerba

The marine dynamic sedimentation in the two cases: northern (Ras R’mel) and southern (Kastil) Djerba - Yamoun, Messaoud (2nd Djerba International Mediterranean Environment Sustainability Conference, 22-25 avril 2012, Atti e Memorie Dell’Ente Fauna Siciliana, 2014)
Keywords: Botanique – Djerba

Sebkhas as ecological archives and the vegetation and landscape history of southeastern Tunisia during the last two millennia - Schulz, E; Abichou, A; Hachicha, T; Pomel, S; Salzmann, U; Zouari, Kamel (Journal of African Earth Sciences, 2002)
Keywords: Botanique – Djerba

Les sites Ramsar de l’île de Djerba - Karem, Abdelhamid (2nd Djerba International Mediterranean Environment Sustainability Conference, 22-25 avril 2012, Atti e Memorie Dell’Ente Fauna Siciliana, 2014)
Keywords: Botanique – Djerba

Institutionelle Analyse von Implementierungshindernissen multilateraler Umweltabkommen: Erklärungsansätze am Beispiel der Ramsar Konvention auf der Insel Djerba - Gouja, Majdi (Shaker Verlag, 2016)
Keywords: Botanique – Djerba

The genus Amphistegina (benthic foraminifera): distribution along the southern Tunisian coast - El Kateb, Akram; Stalder, Claudio; Stainbank, Stephanie; Fentimen, Robin; Spezzaferri, Silvia (BioInvasions Records, 2018)
The benthic foraminiferal genus Amphistegina is currently expanding its range in the Mediterranean Sea after being introduced through the Suez Canal from the Red Sea. Over the previous decade, Amphistegina spp. has colonized the eastern part of the Mediterranean Sea including the Egyptian and Libyan coasts, but the present southern limit in the Mediterranean Sea is along the southern Tunisian coast. However, this limit has never clearly been defined, and existing models predict an expansion along the entire Tunisian coastline. The Gulf of Gabes, in the southern part of Tunisia, is heavily polluted by local phosphate industries that discharge untreated waste directly into the sea. Amphistegina spp. is sensitive to water quality and marine pollution. Based on our surveys and recent investigations, the present distribution area of Amphistegina spp. along the south Tunisian coast includes the coastline east of Djerba Island, located in the Gulf of Gabes. Possible limiting factors for Amphistegina spp. expansion in the Gulf of Gabes may be the unfavourable environmental conditions generated by the phosphate industry. Kateb, Akram El; Stalder, Claudio; Stainbank, Stephanie; Fentimen, Robin; Spezzaferri, Silvia
Keywords: Botanique – Djerba

Ipotesi di reimpianto e bioremediation attraverso l’utilizzo di Smongia officinali Linnaeus 1759 coltivata a Djerba (Tunisia) e reimpiantata nelle Aree ad Elevato Rischio di Crisi Ambientale della Sicilia (Italia) - Pitruzello, Francesco; De Angelis, Elisa (2nd Djerba International Mediterranean Environment Sustainability Conference, 22-25 avril 2012, Atti e Memorie Dell’Ente Fauna Siciliana, 2014)
Keywords: Botanique – Djerba

Analyse de la composition minérale de différents cultivars de palmier dattier de l’ile de Djerba - Moussa, Majida (Institut Supérieur des Etudes Technologiques, 2005)
Keywords: Botanique – Djerba

Observations on the flora of brackish coastal environments of Augusta (Sicily), Priolo G. (Sicily) and Djerba (Tunisia) - Mangiafico, Rosalia (2nd Djerba International Mediterranean Environment Sustainability Conference, 22-25 avril 2012, Atti e Memorie Dell’Ente Fauna Siciliana, 2014)
Keywords: Botanique – Djerba

Les analyses statistiques multivariées : application sur deux espèces de Soleidea des cotes Tunisiennes - Glid, A. (Bulletin de l’Institut National des Sciences et Technologies de la Mer, 2009)
Keywords: Botanique – Djerba

Etude de la variabilité génétique chez différents cultivars de palmier dattier de l’île de djerba - Elouni, Sami (Faculté Des Sciences de Sfax, 2006)
Keywords: Botanique – Djerba

Elimination of bacteria from in vitro shoot cultures of "Douce de Djerba", a micropropagated apple cultivar - Marín, J. A.; Boudabous, Manel; Lorente, P.; García, E.; Andreu, P.; Arbeloa, A. (ITEA (Información Técnica Económica Agraria) (España), 2010)
Keywords: Botanique – Djerba

Chromosome number and genome size in Atriplex mollis from southern Tunisia and Atriplex lanfrancoi from Malta (Amaranthaceae) - Tlili, Abderrazak; Gouja, Hassen; Vallès, Joan; Garnatje, Teresa; Buhagiar, Joseph; Neffati, Mohamed (Plant Systematics and Evolution, 2020)
Keywords: Botanique – Djerba

Salt tolerance of the annual halophyte Cakile maritima as affected by the provenance and the developmental stage - Megdiche, Wided; Ben Amor, Nader; Debez, Ahmed; Hessini, Kamel; Ksouri, Riadh; Zuily-Fodil, Yasmine; Abdelly, Chedly (Acta Physiologiae Plantarum, 2007)
Though halophytes are naturally adapted to salinity, their salt-tolerance limits are greatly influenced by their provenance and developmental stage. In the present study, physio-biochemical responses of two Tunisian ecotypes of the oilseed coastal halophyte Cakile maritima (Brassicaceae) to salinity (0–400 mM NaCl) were monitored during germination and vegetative growth stages. Tabarka and Jerba seeds were collected from humid or arid climatic areas, respectively. Plant response to salinity appeared to depend on the ecotype and salinity levels. Increasing salinity inhibited germination process. Jerba seeds were found to be more salt tolerant than the Tabarka ones. At the autotrophic stage of growth and under salt-free conditions, Jerba was less productive than Tabarka (in terms of dry matter accumulation), but plant biomass production and leaf expansion (area and number) of the former ecotype were progressively improved by 100 mM NaCl, as compared to the control. In contrast, at the same salt concentration, these parameters decreased under increasing salinity in Tabarka (salt sensitive). Leaf chlorophyll content was reduced at severe salinity, but this effect was more conspicuous in the sensitive Tabarka plants. Na+ contents in the Jerba and Tabarka leaves collected from the 400 mM NaCl-treated plants were 17- and 12-fold higher than in the respective controls. This effect was accompanied by a significant reduction in the leaf K+, Mg2+ and Ca2+ contents, especially in the salt-treated Tabarka. A significant accumulation of proline and soluble carbohydrates in leaves was found during the period of intensive leaf growth. These organic compounds likely play a role in leaf osmotic adjustment and in protection of membrane stability at severe salinity.
Keywords: Botanique – Djerba

Physico-Chemical Characterization and Analysis of Various Tunisian Olive Oil Varieties: Minor Compounds and Fatty Acids - Slim, Smaoui; Hajer, A; Ben-Hlima, Hajer; Jarraya, Raoudha; Kamoun, Nozha; And, Raoudha; Mohamed, Damak (Journal- Chemical Society of Pakistan, 2012)
Given the growing interest of consumers worldwide in safe, healthy and good quality olive oil, the present study aimed to investigate a number of Tunisian virgin olive oil varieties in an attempt to procure physico-chemical characteristics of interest to the local and global olive oil industry, particularly in terms of variety and area of cultivation. Eight samples collected from Chetoui, Chemlali, Zarrazi, and Zalmati Tunisian cultivars located at Sfax, Thibar, Zarzis, and Jerba were employed. Various physic-chemical parameters were investigated, including free acidity, peroxide value, UV absorption, pigment concentrations, oxidative stability, fatty acid composition, phenolic compounds and sterols. The findings revealed high heterogeneity within and between the varieties. The Chemlali Jerba" and Zarrazi oil samples showed high oleic acid and low linoleic acid concentrations, rich phenolic compounds, and high stability. The sterols fractions in Chemlali Sfax, Chemlali Jerba, and Zalmati olive oils displayed high levels of β-sitosterol, campesterol, and ∆-5-avenasterol. Overall, the olive oil from Chemlali Jerba presented higher levels of natural antioxidants and oxidative stability. Its chemical composition was also noted to be particularly interesting in terms of fatty acid contents, minor components, and antioxidants, namely sterols, tocopherols, carotenoids, and phenolic acids.
Keywords: Botanique – Djerba

Etude morphologique physiologique et biochimique comparée de quelques cultivars d’orge (Hodeum vulgare L.) de l’ile de Djerba soumis au stress hydrique - Zarrouk, Kawthar (Faculté des Sciences de Tunis, 2012)
Keywords: Botanique – Djerba

Conservation et valorisation d’une variété de pommier cultivée dans les regions arides tunisiennes (la douce de Djerba) - Boudabous, Manel (Faculté des Sciences de Tunis, 2007)
Keywords: Botanique – Djerba

la variété de pommier douce de Djerba : caractérisation chimique et essais de culture in vitro - Boudabous, Manel (Université de Tunis El Manar, 2005)
Keywords: Botanique – Djerba

Etude de la variabilité génétique de deux cultivars du palmier dattier endémiques de l’ile de Djerba “Lemsi” et “Mattata” - Ben Marzouk, Insaf (Faculté des Sciences Mathématiques, Physiques et Naturelles de Tunis, 2007)
Keywords: Botanique – Djerba

Analysis of the essential oil of Artemisia campestris L. - Akrout, Ahmed; Chemli, Rachid; Chreïf, Imed; Hammami, Mohamed (Flavour and Fragrance Journal, 2001)
The composition of the essential oil obtained by hydrodistillation from the aerial parts of several populations of Artemisia campestris L. (Asteraceae), collected from four areas of south-eastern of Tunisia (Bengardane, Benikhdache, Jerba and Tataouine), was analysed by GC–MS. Thirteen to fifteen components were identified in each sample, representing more than 95% of the total oil. All samples were dominated by the presence of β-pinene (24.2–27.9%), p-cymene (17.4–22.3%) and α-pinene (4.1–11.0%), representing more than 45% of the total oil. The distribution of other components in the different extracts was qualitatively and quantitatively irregular. The variability of the composition can be attributed to the climatic and geographical conditions among areas
Keywords: Artemisia campestris L. – Djerba; Botanique – Djerba

Une grande figure de la botanique belge a disparu, le Professeur Constant Vanden Berghen (21 mai 1914 - 5 novembre 2004) - Peeters, Alain (Systematics and Geography of Plants, 2005)
Keywords: Botanique – Djerba

Genetic diversity in local barley accessions collected from different geographical regions of Tunisia - Ould Med Mahmoud, M. A.; Hamza, S. (Plant Genetic Resources, 2009)
Keywords: Botanique – Djerba